Study of the Physicochemical Properties of Recycled PVX - Sirgiyevich, Rosilov Mansur; o‘g‘li, Sirojiddin Alpomish (International Journal on Economics, Finance and Sustainable Development (IJEFSD), 2023)
Recycling waste PVХ compared to polyolefins is a bit difficult, so the products made from them have a complex chemical composition, that is, various additives will be added. Given these problems, it is possible to obtain various types of secondary products, modifying them by adding special components that facilitate the processing of PVC waste.